2011
DOI: 10.1111/j.1939-1676.2011.00799.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of a Novel Lipophilic Formulation of Methimazole for the Once Daily Transdermal Treatment of Cats with Hyperthyroidism

Abstract: Background: Previous studies on transdermal methimazole have used pluronic lecithin organogel as the vehicle. This might not be the most suitable vehicle for a lipophilic drug, such as methimazole.Hypothesis/Objectives: Once daily transdermal administration of a novel lipophilic formulation of methimazole is as safe and effective as oral carbimazole in treating hyperthyroidism in cats.Animals: Forty-five client-owned cats diagnosed with hyperthyroidism. Methods: Prospective study. Cats with newly diagnosed, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 42 publications
1
55
0
Order By: Relevance
“…However, after local methimazole administration, a species-specific reaction to the is demonstrated. In humans, it induces skin discoloration (17) and inhibits keratinocyte proliferation (7), which was not observed in cats (15). A significant influence of methimazole on melanocyte functions appears (17,19) despite the lack of cytotoxicity even in high concentrations (2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, after local methimazole administration, a species-specific reaction to the is demonstrated. In humans, it induces skin discoloration (17) and inhibits keratinocyte proliferation (7), which was not observed in cats (15). A significant influence of methimazole on melanocyte functions appears (17,19) despite the lack of cytotoxicity even in high concentrations (2).…”
Section: Discussionmentioning
confidence: 99%
“…Methimazole (1-methyl-2-mercapto imidazole) is an antithyroid drug used worldwide as the first choice in chronic treatment of hyperthyroidism in humans (31), dogs (39), and cats (15,16,21,28,29). Its mechanism of action is similar to other thioamides that block the activity of thyroperoxidase, leading to reduced biosynthesis of thyroid hormones; however, uncontrolled methimazole treatment (overdosing) results in hypothyreosis (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transdermal methimazole was often used by respondents to our survey. It is thought to improve client compliance, 14,25 but a study evaluating long-term transdermal methimazole use found 17% of owners admitted not treating their cat regularly, suggesting compliance may still be suboptimal. 26 Adverse reactions of anti-thyroid medications were consistent with previous reports.…”
Section: Factormentioning
confidence: 99%
“…It also protects tissues against lipid peroxidation, stimulating the mechanisms of the antioxidant system (16,23,35). Methimazole is an anti-thyroid drug commonly used around the world in the long-term treatment of hyperthyroidism in humans (11,15,27,39), dogs (37), and cats (12,13,18,24,25,36). Like in other thionamides, its mode of action is based on blocking the activity of thyroid peroxidase, which leads to a decrease in the synthesis of thyroid hormones (6).…”
mentioning
confidence: 99%